IMPACT OF PHARMACIST LED HYPERTENSION MANAGEMENT - MATHEWS, ANJU SARAH; KUMARI, SRESHI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The study objective was to analyze the effect of pharmacist interventions in improving blood pressure control. Methods: The prospective interventional study was conducted on a population who were known hypertensive for more than 2 years. They were randomly categorized into two groups, interventional group and usual care group. Pharmaceutical care, involving telephonic follow-up, adherence analysis, patient education was given in the former group in a time interval of 2 months for about 12 months while the later was on regular therapeutical care only. Blood pressure was monitored in each follow-up. The difference in control of blood pressure was measured in terms of mm/Hg unit. The improvement in the measure from start and end of the study was analyzed within the group and between the groups. Results: Lowered blood pressure was observed in both the groups in the end of study. But statistically significant difference was seen in interventional group compared to the other. Involvement of pharmacist led care helped in achievement of AHA goal. Conclusions: Including clinical pharmacist in a health-care team can provide unerring therapeutic regimen to patients thereby their health-care outcome.